2005
DOI: 10.2298/jsc0501041j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and electrocatalytic application of silver modified polypyrrole electrodes

Abstract: Silvermodified polypyrrole electrodes were prepared with the aim of testing them for the electro oxidation of formaldehyde in alkaline solution. The modification of polypyrrole by immersion in aqueous AgNO3 solution was studied by cyclic voltammeter and vacuum techniques (AES and XPS). The influence of time of immersion and the thickness of the polypyrrole film, prepared by electrochemical polymerization, on the modification of the polymer were examined. The results acquired from both electrochemical and spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
1
8
0
1
Order By: Relevance
“…Also, bare GC was immersed in 0.01 M AgNO 3 solution during the same time as when coated with PVC membrane, but the response to Ag + this time was far from Nernstian. Thus, it was concluded that the polymeric membrane retained its response to silver ions and bearing in mind our earlier results 14, 15 we assumed that the PVCAc membrane was modified by silver.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Also, bare GC was immersed in 0.01 M AgNO 3 solution during the same time as when coated with PVC membrane, but the response to Ag + this time was far from Nernstian. Thus, it was concluded that the polymeric membrane retained its response to silver ions and bearing in mind our earlier results 14, 15 we assumed that the PVCAc membrane was modified by silver.…”
Section: Resultsmentioning
confidence: 54%
“…As can be seen this electrode has the best response to the silver cation, better than to other species. We showed earlier that GC as well as polypyrrole (PPy) could be modified by silver simply by immersion of the electrode in silver nitrate solution 14, 15. So, in order to distinguish whether the response of PVC membrane to silver ions was due to membrane modification or possibly from the modified GC support, the comparable membrane of the same composition was coated on Pt wire.…”
Section: Resultsmentioning
confidence: 99%
“…[57][58][59]. Usually used substrates for polymer deposition are electrodes made of graphite, carbon fibers, glassy carbon, Indium-tin oxide (ITO), inert metals like Au and Pt [11,43,[60][61][62][63][64][65].…”
Section: Scheme 1 -Electrochemical Polymerization Of Pyrrolementioning
confidence: 99%
“…Most of the studies in this field concern the deposition of noble metals Au [16,[210][211][212][213][214][215][216][217][218][219][220][221][222], Ag [223][224][225][226][227][228][229][230][231][232][233][234][235], Pd [156,158,[236][237][238][239][240][241][242][243][244][245][246][247][248], Pt [249,250] and Hg [251,252], with equilibrium potentials that are positive enough with respect to the potentials of oxidation transitions in most CPs, e.g. PANI, PPY etc.…”
Section: Use Of the Polymer Materials As Reductantmentioning
confidence: 99%